EBT3-based dosimeter in characterizing UVA–LEDs with lambertian radiation pattern. Issue 4 (15th July 2019) - Omar, Ahmad Fairuz; Chiong, Wan Long; Tan, Wei Yee; Wong, Jia Wen
Abstract : Purpose: This paper aims to propose an area under the curve model to represent ultraviolet (UV) exposure doses on EBT3 films (in mJ/cm 2 ). The model was developed on a cross-section of the exposed films using visible absorbance method. Ultraviolet–A light emitting diodes (UVA–LEDs) with 20° and 60° half angle with distinctive peak emission wavelengths between 365 to 405 nm are used in this experiment. No similar experimental setup or findings have been reported thus far, though the various application of EBT3 for the measurement of solar UV (A + B) have been published since EBT3 is commercially available. Design/methodology/approach: Two sets of UVA–LEDs were used as the UV radiation source in the experiment. The first set contains of four 5 mm low power UVA–LEDs with the 20° half angle and peak emission wavelength at 365, 375, 385 and 400 nm. The second set contains of five surface mount high power UVA–LEDs with the 60° half angle and peak emission wavelength at 365, 375, 385, 305 and 400 nm. The illumination setup for the two sets of LEDs is different between each other to obtain sufficient dose distribution on the films for spectroscopy analysis. This is due to the different illumination angle and irradiance intensity by each set of LEDs. Findings: UV–LED with a peak emission of 365, 375 and 385 nm able to produce UV doses accurately measurable using EBT3 films, UVA–LEDs with peak emission at 395 nm and above produced much lower accuracy with R 2 . From both set of LEDs, it can be concluded that peak emission wavelength of UVA–LED does influence the discoloration of the films. Shorter wavelength (higher energy) of UVA–LEDs discolors EBT3 films much intense compared to longer wavelength for a given UV dose exposure. Originality/value: Despite various practical applicability and advantages of UV–LEDs, there are still no standard methods in measuring UV–LED radiation output. The proposed approach not only allows us to obtain the dose of UV–LED, where the sensitivity of measurement is wavelength (energy) depended but also allows us to visually observe the illumination pattern of invisible UV radiation through the application of EBT3 films.